Establishment and characterisation of a novel canine mast cell tumour cell line (C18) - Sudchaya Bhanpattanakul; Supranee Buranapraditkun; Theerayuth Kaewamatawong; Patharakrit Teewasutrakul; Sirintra Sirivisoot; Panida Poonsin; Anudep Rungsipipat; Praopilas Phakdeedindan; Takayuki Nakagawa; Achariya Sailasuta; Theerawat Tharasanit (BMC Veterinary Research)
Abstract Background Mast cell tumour (MCT) is a life-threatening neoplasm commonly found in dogs worldwide. The outcome of treatment for dogs with cutaneous MCT is currently poor, mainly because of the tumour’s aggressiveness and the heterogeneity in tumour behaviour. This study established a novel canine MCT cell line and compared with three reference canine MCT cell lines (CMMC, VIMC and CoMS) in terms of their characteristics and tumour sensitivity to immune cell-mediated cytotoxicity. Results Of 18 MCT samples, only one cell line derived from high grade cutaneous MCT was established and referred to as C18 cell line. The C18 cell line could be maintained for over 100 passages while they still exhibited c-kit, tryptase, FcεRIα and FcεRIβ expression. The C18 had the longest doubling time and smallest tumour spheroid size when compared to the other three reference cell lines. The C18 also had c-kit internal tandem duplication (ITD) in exon 11 and nine single nucleotide polymorphisms (SNPs) in five genes, namely c-kit, HYAL4, SEL1L, SPAM1 and TRAF3. For a comparison of tumour sensitivity to immune cell-mediated cytotoxicity, the percentages of early and total apoptotic cells were significantly increased in all four cell lines. However, the percentages of viable cells were significantly decreased only in C18. Conclusion In conclusion, a novel canine cutaneous MCT cell line was successfully established, in terms of its characteristics, growth behavior and interaction with PBMCs. The C18 cell line holds a potential promise for advancing studies and developing new therapeutic strategies.